The Effect of Brand Ambassadors and Logo Design on Repurchase Interest through Consumer Trust as a Mediating Variable in Tiebymin Hijab Products on TikTok Shop - Yesi Safitri; Dadan Abdul Aziz Mubarok (International Journal of Marketing & Human Resource Research, 2026)
The growth of live commerce on TikTok Shop has encouraged hijab businesses to strengthen marketing strategies through promotional figures and brand visual identity. This study examines the effects of Brand Ambassadors and Logo Design on repurchase intention through consumer trust for Tiebymin hijab products, particularly following a logo redesign that elicited varied consumer responses. A quantitative explanatory approach was applied, collecting data from 100 consumers through an online 1–5 Likert-scale questionnaire using purposive sampling. Data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) via measurement and structural model evaluation. Findings indicate that Brand Ambassadors and Logo Design positively influence Consumer Trust, which mediates and reinforces their impact on Repurchase Intention. These results highlight that repurchase decisions in live-commerce depend not only on promotional appeal and visual identity but also on consumer confidence in the brand. Businesses are advised to select Brand Ambassadors aligned with brand character and to maintain consistent logo design; future research may include additional factors to expand understanding of repurchase behavior.